KAJIAN AWAL PEMANFAATAN AIR LAUT UNTUK EKSTRAKSI LIMBAH CAIR CPO DALAM MENURUNKAN KADAR MINYAK DAN LEMAK, ANGKA BOD, ANGKA COD SERTA NILAI pH - Hasan Basri Daulay; Yusril Dhani; Riri Yulianti (Jurnal Agroindustri, 2011)
Palm oil mill (POM) is an industry laden with residues of processing. From the processing of fresh fruit bunches into crude palm oil (CPO) industrial wastewater treatment using pond systems that are not yet qualified a lot of quality raw wastewater. This study aims to determine the ability of sea water in the lower levels of oil and fats, the rate of COD and BOD and pH in wastewater CPO, determine the most optimal ratio in the extracrion process of palm oil wastewater with seawater in reducing chemical properties in terms of oil content and fat, the rate of COD and BOD and pH in wastewater re-CPO and to utilize the extracted oil as raw material for making soap cream. Liquid waste is liquid wate used palm oil (first pond). The treatments in this experiment were 5 treatments and 3 replication, one-time treatments of liquid waste CPO mixing with seawater. By compration of 9:1, 4:1, 7:3, 3:2, and 1:1 ml of water can reduce the oil-fat content of the original 384 mg/L to 372-22 mg/L, COD of 13700 mg/L became 10290-860 mg/L, the rate of BOD of 4700 mg/L to 2100-95 mg/L and pH values from 6.5 to 6.43 to 5.23. Comprasion of crude palm oil wastewater with seawater optimal in reducing the oil-fat levels, the rate of COD and BOD as well as the pH value is a ratio of 1:1 for of quality of industrial wastewater. Separation power of sea water to the oil-fat content is 3.1 to 94.27% of 384 mg/L, 4700mg/L and the extracted oil can be made as a raw material for making soap